ROCK FRACTURES NEAR FAULTS: SPECIFIC FEATURES OF STRUCTURAL‐PARAGENETIC ANALYSIS - Yu. P. Burzunova (Геодинамика и тектонофизика, 2017)
The new approach to structural‐paragenetic analysis of near‐fault fractures [Seminsky, 2014, 2015] and specific features of its application are discussed. This approach was tested in studies of fracturing in West Pribaikalie and Central Mongolia. We give some recommendations concerning collection, selection and initial processing of the data on fractures and faults. The analysis technique is briefly described, and its distinctive details are specified. Under the new approach, we compare systems of natural fractures with the standard joint sets. By analysing the mass measurements of the orientations of joint sets in a fault zone, it becomes possible to reveal the characteristics of this fault zone, such as its structure, morphogenetic type, etc. The comparative analysis is based on the identification of the main fracture paragenesis near the faults. This paragenesis is represented by a triplet of mutually perpendicular joint sets. The technique uses the qualitative approach to establish the rank hierarchy of fractures and stress fields on the basis of genetic subordination. We collect and analyse the data on tectonic fractures identified from a number of indicators, the main of which are the geometric structure of the (systematic or chaotic) fracture system, and shear type of fractures. The new technique can be applied to analyse other genetic types of fractures (primary, hypergenic), provided that tectonic stresses were significantly involved in fracturing, which is evidenced by the corresponding indicators. Methods for conducting geological and structural observations are uniform for all sites and points, and increasing the number of observation points provides for a more effective use of the new technique. In our paper, we give specific parameters for constructing circle fracture diagrams. All the maximums in the diagram are involved in the analysis for comparison with the standard patterns. Errors caused by random coincidence are minimized by using special criteria to estimate the diagrams, and the reliability of the solutions is thus ensured. This paper considers various problems related to interpretations of natural fracture systems, concerning the angles between the conjugate joint sets, the presence of non‐standard fracture parageneses, fault zones of mixed types, and structural‐material inhomogeneities. The recommendations based on our experience of selection and processing of input field data can be viewed as a sup‐ plement to the method of analysis used for specialized mapping of faults zones and detection of stress fields [Seminsky, 2014, 2015]. The discussed information can be useful for those who are willing to successfully use this new approach to investigate the fault systems in the upper crust and solve applied and fundamental problems in the studies of faulting.